The Effect of the Leadership Perception and Organizational Justice on Organizational Commitment: A Research in a State University - Taner, Bahar; Turhan, Mithat; Helvacı, Ilter; Koprulu, Onur (International Review of Management and Marketing, 2015)
Each individual is directly or indirectly in the position of being a member of the organization. At this point, carrying on their activities successfully and reaching their determined goals will probably bring about some gains both for the organizations and the employees. It is stated that employees’ high level of organizational commitment is related to the managers who take people into consideration, have a supportive and participative leadership approach, agree with the decisions taken and who is fair in the distribution of gains. The purpose of this study is to determine the interaction between leadership perception, organizational justice and commitment. Questionnaire method was used for data collection. The collected data was analyzed with the statistical methods. The sample of this study consists of 683 academic and administrative staff personel. Keywords: Leadership; Organizational Justice and Commitment; Structural Equation Model JEL Classifications: M100; M120